Handbook of public opinion research - Donsbach, Wolfgang, 1949-; Traugott, Michael W. (London : SAGE, 2007)
An indispensable resource for both practitioners and students alike, the handbook brings together a review of what public opinion is, what role it has in a society, how it changes and by what it is affected, how it can be measured and what impact it has.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Public opinion; Public opinion polls